Use of Duplex Ultrasound for Evaluation of Complex Aortic Arch Vessel Re-routing for Thoracic Endovascular Aneurysm Repair. Issue 3 (September 2015) - Liu, Anyi; Wartak, Siddharth; Srivastava, Sunita; Roselli, Eric E.; Whitelaw, Susan; Gornik, Heather L.
Introduction: Technological advances have increased availability of endovascular therapies for complex aortic disease. Endovascular repair of thoracic aortic aneurysms (TEVAR) involving the arch and proximal descending thoracic aorta is challenging with respect to the proximal landing zone for fixation of the endograft and prevention of endoleak. In such cases, additional vascular procedures may be necessary for re-routing of arch vessels. Patient Description: An 88 year-old man was treated for chronic type B aortic dissection with aneurysm and rapid growth, including involvement of the distal aortic arch (arch 6.5 cm, descending thoracic aorta 6.2 cm). He underwent a left common carotid artery (CCA) to subclavian artery (SCA) bypass followed by a second bypass procedure communicating the right CCA to the left CCA–SCA graft. A thoracic endograft was placed which covered the origin of the left SCA and left CCA with distal fixation just above the celiac artery. Two weeks after the surgery, he developed confusion and a carotid duplex study was conducted using a Philips iU22 with a 9-3 MHz linear transducer. Findings: Both synthetic bypass grafts were well visualized and were widely patent with no velocity shifts indicative of stenosis. The right to left graft ran behind the esophagusbefore its anastomosis to the left CCA–SCA graft. A dissection flap and small, partially thrombosed pseudoaneurysm were visualized at the right internal carotid artery (ICA) origin consistent with prior carotid dissection, but there was no evidence of stenosis. A plaque was visualized in the left ICA with a velocity shift noted consistent with moderate stenosis. The vertebral arteries were patent with antegrade flow, although flow in the left vertebral artery had a delayed upstroke, likely reflecting the long re-routing of blood flow. Conclusion: Vascular technologists may be called to assist in the care of patients who have undergone re-routing of the aortic arch vessels for TEVAR. The complex anatomy of these cases emphasizes the importance of preparation for the examination, including review of operative reports and communication with referring clinicians.